The Concept of Integrated Quality Management Applicative Studies - Muhammad Solikhin; Suwadi Suwadi (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
This article explores the application of integrated quality management in building Islamic educational institutions that can produce actual figures as educational institutions providing a pilot impact in the surrounding environment and strengthening Islamic Science. The Madrasah Diniyah Takmiliyah Az-Ziyaadah was analysed using a descriptive qualitative method. Meanwhile, the data were collected through interviews, observations, and documentation studies. The interview was conducted with key informants, namely the principal, ustadz, ustadzah, and education observers. Secondary data sources were in the form of documentation of learning in Madrasah Diniyah Takmiliyah Az-Ziyaadah. Furthermore, the data analysis technique refers to the concept of Miles and Huberman. The result showed that the application of quality management in the Madrasah Diniyah Takmiliyah adopts Islamic values, systematic revitalisation of human resources, and a system of rules. In Islamic values, it refers to integrating the concept of integration with the importance of the Qur'an. In the systematic revitalisation of human resources, steps are performed for restoration, regeneration, quality of human resources, strengthening finances, and networking.